The disappearing [large type] : a novel - Roy, Lori (Wheeler Publishing, a part of Gale, a Cengage Company, 2018)
After leaving her cheating husband in New York City and returning to her family's historic Florida plantation, Lane Fielding's oldest daughter disappears, reigniting her memories and fears of a serial killer who traumatized the area in the 1970s.